2019
DOI: 10.33045/fgr.v35.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Fruits Physico-Chemical Parameters of Some Romanian Kiwifruit Hybrids Influenced by Different Cold Storage Technologies

Abstract: Kiwifruit is recognized as highly nutritious having many biochemical characteristics that deliver a range of health benefits. In Romania, kiwi is a new fruit species and the creation, testing and introduction of winter hardy genotypes, adapted to the local harsh climate conditions is a priority. A common Italian-Romanian kiwifruit breeding program was initiated in 1993 and during the time, several hybrid genotypes were obtained and introduced to be tested. After more than two decades of research, it was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Park et al [38] also noted a significant difference in ascorbic acid content among various kiwifruit cultivars. It is worth noting that the measured values of ascorbic acid in our study exceeded those reported in previous ones [24,30,34,39]. According to Esti et al [40], factors such as genotype, ripening stage, storage conditions, and the analytical technique employed, can influence the ascorbic acid content of kiwifruit.…”
Section: Parameterscontrasting
confidence: 62%
See 1 more Smart Citation
“…Park et al [38] also noted a significant difference in ascorbic acid content among various kiwifruit cultivars. It is worth noting that the measured values of ascorbic acid in our study exceeded those reported in previous ones [24,30,34,39]. According to Esti et al [40], factors such as genotype, ripening stage, storage conditions, and the analytical technique employed, can influence the ascorbic acid content of kiwifruit.…”
Section: Parameterscontrasting
confidence: 62%
“…Following the findings of Stec et al [23], Jaeger et al [3] concluded that commercial Actinidia fruits with firmness ranging from 0.6 to 0.8 Kg (approximately 5.9 N to 7.8 N) were significantly more acceptable to consumers. Furthermore, the life storage of kiwifruit is affected by the extent to which the flesh softens [24] and this was obvious in the present study, as both genotypes presented a significant reduction in fruit firmness during both years. According to Krupa [25], kiwifruits are considered ripe and ready to be consumed when the firmness of the flesh measures below 9.81 N.…”
Section: Resultsmentioning
confidence: 50%